Ocurrency of Eimeria spp in domestic rabbits (Oryctolagus cuniculus) in four counties at the north Paraná State - Cardoso, Marco Antonio; Guimarães Junior, José da Silva (Semina: Ciências Agrárias, 1993)
<!–[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> To acertain which species of Eimeria are causing natural infections in rabbits breed for commercial purposes at the north of the State of Paraná, in South Brazil, 109 faecal sample were collected from four counties of such region: Londrina, Cambé, Ibiporã and Jataizinho. The inquiry was conducted in August and September, 1990; the laboratorial processing and microscopical examinations of those samples showed that the Eimeria species infecting rabbits and their relative prevalences were: E. perforans (36,76%), E. coecicola (19,78%), E. stiedai(12,18%), E. magna (9,24%), E. intestinalis (9,18%) E. irresidua (7,18%), E. flavescens (5,41%), and E. media (0,33%); 72,48% of all samples were positive for at least one of these species of Eimeria. The arrangement of the hosts into four age-classes did not conduct to any significant difference between classes in wat concerns numbers of oocysts per gram of faeces.